Challenges to professionalism and ethics in perioperative clinical practice. (2nd May 2021) - Kumar, Bid
Abstract : Perioperative medicine can pose myriad challenges to professionalism and ethical practice. Medicine is a science, but definite end points, and predictable results and outcomes do not consistently occur. There is the potential for error during all steps of a patient's assessment and treatment. Examination findings, laboratory investigations, diagnosis, plans for and outcomes of surgery and long-term outcomes can all be uncertain and/or not meet expectations. Factors including pressures in the workplace, conflicts, ego, prescribed guidelines and pathways, the need to achieve healthcare targets, desire for autonomy and need to maintain multidisciplinary involvement in patient care can lead to an environment in which it is challenging for professionalism and ethics to thrive.